Process optimization for enhancing interconnect performance of large-size BGA component during vibration loading. (March 2022) - Cong, S.; Zhang, W.W.; Liu, P.; Han, Y.N.; Tian, Y.H.
Abstract: A series of problems such as failure solder at SnAgCu large-size BGA component and Pb-rich phase at SnPb component are always found during mixed lead-free/tin-lead assembly. In order to give a better reflow process window of assembled printed circuit board, process optimization was carried out to satisfy a favourable reflow time for all the components. Numerical simulation according to the Box-Behnken design method was carried out to monitor the effective reflow time of mixed lead-free/tin-lead and tin-lead components, and a mathematical response model between the effective reflow time and the process curve was developed by multivariate quadratic regression analysis. An optimal reflow process curve was established by simulated annealing algorithm. According to the optimal process parameter, numerical simulation was carried out to observe the temperature distribution and residual stress, and the experimental researches including the vibration test and micro structure analysis were conducted on the mixed lead-free/tin-lead assembled component to monitor the dynamic resistance and deformation and characterize the reaction product at the interface. It is shown that the corner BGA component still suffers from both a higher residual stress (about 32 MPa) after reflow process and a larger deformation (about 64 μm) at the first order modality during random vibration test. However, a continuous intermetallic compound layer with the thickness of 1.2–1.5 μm containing the reaction products Ni3 Sn4 and (Au, Ni)Sn4 is well generated, and no cracks and voids are observed.